La médiation paysagère au prisme de la recherche-action : éléments de réflexion - Samira Khettab (Projets de Paysage)
Approaching the territory through the landscape is a productive approach allowing the sharing of decision-making between local actors, and in particular through reinforcing the role of non-institutional actors and non-organized civil society. This article focuses on landscape mediation from the perspective of research and action-research providing examples of landscape mediation examined via a conceptual framework. The findings reveal certain contradictions between discourse and practice, not in terms of the democratic process but rather in terms of the operational scope of the approach.